UPAYA PENINGKATAN KEMAMPUAN MENARI TARI TOPENG GUNUNGSARI PADA MAHASISWA JURUSAN PENDIDIKAN SENI TARI DENGAN PENDEKATAN APRESIASI SENI DAN LATIHAN SECARA RUTIN - herlinah herlinah (Imaji, 2012)
!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} -- Abstract The research was purposed to make efforts to improve Dance Education Department student dancing abilities of Topeng Gunungsari Dance by Art Appreciation method and practiced routinely. The research used design models which were developed by Kemmis Mc. Taggart consisted of four components included: planning, action, observation, and reflection. The researchers planned and established action types which would be done, that were: student practiced together by masks, and watched a Topeng Gunungsari Dance performance by video recording routinely. The research result of dance studying was that by the practiced and watched a Topeng Gunungsari Dance video recording routinely could improve dancing abilities of Topeng Gunungsari dance. Key words: dancing ability, art appreciation, routine practice.